HISTORY OF THE DEVELOPMENT OF RADIOTHERAPY AS AN EXACT SCIENCE - Kurbankulov Uktam; Ismailova Umida; Khamidov Khojiakbar (PEDAGOGS, 2024)
Abstract. The development of radiation therapy technologies in oncology from its origins to the present day is associated with the desire to ensure high accuracy of dose delivery to the tumor for receipt the greatest effect With minimal toxicity. The development of radiobiology has determined the possibilities of choosing optimal irradiation schemes and modes, taking into account the radiobiological characteristics of neoplasms. Achievements modern radiotherapy - This result perennial works, research and discoveries, result implementations brave ideas several generations scientists and engineers, physicists And doctors. IN article reflected most significant events in the history of the use of various types of ionizing radiation that became fundamental For formations modern remote And contact radiation therapy.